(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Systemic lupus erythematosus (SLE) is very rare and difficult to diagnose before 5 years of age. We are reporting a case of SLE at 2.5- year who presented with recurrent episodes of fever, haematuria , proteinuria and rash . Diagnosis of SLE was confirmed by reduced serum complement level and positive anti double stranded DNA (anti ds DNA). Class IV histological type of Lupus nephritis was evaluated by renal biopsy DOI: 10.3329/jbcps.v28i1.4647 J Bangladesh Coll Phys Surg 2010; 28: 59-62